Proceedings of the 13th International Conference on Mining Software Repositories 2016
DOI: 10.1145/2901739.2901762
|View full text |Cite
|
Sign up to set email alerts
|

Inter-app communication in Android

Abstract: The Android platform is designed to support mutually untrusted third-party apps, which run as isolated processes but may interact via platform-controlled mechanisms, called Intents. Interactions among third-party apps are intended and can contribute to a rich user experience, for example, the ability to share pictures from one app with another. The Android platform presents an interesting point in a design space of module systems that is biased toward isolation, extensibility, and untrusted contributions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Researchers have also contributed to improve the security of the Android ecosystem by analyzing security vulnerabilities and proposing improvements to current security models [12], [16], [17], [22], [25]- [32], [32]- [35]; however, while the focus of the academic research has been the security of the applicationsthe closest component to the user-, the core of the Android ecosystem (i.e., the Android OS) has received little attention.…”
Section: A Malware and Vulnerabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have also contributed to improve the security of the Android ecosystem by analyzing security vulnerabilities and proposing improvements to current security models [12], [16], [17], [22], [25]- [32], [32]- [35]; however, while the focus of the academic research has been the security of the applicationsthe closest component to the user-, the core of the Android ecosystem (i.e., the Android OS) has received little attention.…”
Section: A Malware and Vulnerabilitiesmentioning
confidence: 99%
“…1) Security in Android Applications: Android malware and vulnerabilities in Android apps are characterized by a novel set of flaws that exploit user level weaknesses and the issues in security mechanisms of the Android OS. For instance, Androidspecific attacks include (i) privileges/permissions escalation through pairs of infected apps that exploit inter-application communication or misconfigured apps [10]- [12], [35], [36], (ii) applications tapjacking/hijacking by apps repackaging and substitution [26], (iii) information leaking through covert channels [37], [38], (iv) SSL vulnerabilities in hybrid [33] and native apps [32], (v) security issues introduced by third party libraries [34], and (vi) security issues introduced by OS customizations [28]. These novel attacks, in addition to classic security attacks induced by malware (e.g., DoS), have been widely studied by the community and several approaches have been proposed for their detection and mitigation, such as TaintDroid [39], COVERT [10], [11], FlowDroid [40], MudFlow [41], Chabada [42], Q-Floid [43], and AppInspector [44].…”
Section: A Malware and Vulnerabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to securing the ICC-based communication, Shekhar et al proposed a separation of concerns to reduce the susceptibility for manipulation of Android apps, by explicitly restricting advertising frameworks [21]. Ahmad et al elaborated on problematic ICC design decisions on Android, and found that missing consistent message types and conformance checking, unpredictable message interactions, and a lack of coherent versioning could break inter-app communication and pose a severe risk [4]. They recommend a centralized message-type repository that immediately provides feedback to developers through the IDE.…”
Section: Related Workmentioning
confidence: 99%
“…The digital forensic used in criminal investigation and evidence, for example, is unproven and is highly criticised in legal proceedings [4]. Such non-rigorous specifications can cause interpretation issues, most commonly developers often choosing undocumented practices that can lead to applications vulnerable to security and privacy threats [1]. A typical consequence of misinterpreting the informal documentation may lead to a scenario where an application developer may incautiously expose a component to third party applications [23].…”
mentioning
confidence: 99%